Learning from Royal Shell’s Logistics and Supply Chain Management - AbdulGhani Gaghman (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
The study is conducted to analysis the supply chain management paying special attention to the logistics. The aim is to understand the impact of logistics on organization performance, also to help in identifying opportunities for cost/time removals and/or value adding along the supply chain. The company chosen for the study is Royal Dutch Shell Plc. As Shell is the one of the big-gest Oil and Gas Company known in the world and one of the leaders of logistic and supply chain management. Though Shell is working efficiently for providing customers with quality services still there are is-sues with the supply chain which should be taken care of in order to be much better. These factors grouped in Control the Cost, Planning and Risk Management, Suppliers/Owners Relationship Management. Study concluded with some suggestions can be adopted by any organization aiming for better performance in supply chain.